A Patient with Chronic Lumbar Pain Diagnosed as Giant Calcified Splenic Hydatid Cyst (Faridpur Medical College Journal, 2020)
Hydatid cyst is a zoonotic disease, caused by Echinococcus Granulosus, mostly found in sheep rearing area of the world but not commonly found in our country. Hydatid disease commonly affects the liver and less frequently the lungs and other organs. Among them splenic hydatid disease has been reported to be 0.5-4%. Here we report a case of a giant calcified splenic hydatid cyst presented with only chronic lumbar pain. A 45 year old female presented with left lumbar pain for the last 1 year. She had no other complaint. She had no pet dog or sheep at home. Physical examination showed no abnormality. A computerized scan revealed a mass in the spleen with round calcification at its margin measuring 7.56×7.96 cm in diameters. Indirect haemagglutination (IHA) for hydatid disease test was negative. Complete blood count, renal and liver function tests were within the normal limit. The patient was clinically diagnosed as splenic hydatid disease and managed by splenectomy after proper immunization. There was a hard calcified mass involving almost whole of the spleen, only thin rim of splenic tissue was present in superior surface. The rest of the abdominal organs including the liver were normal. Total splenectomy was done. Post operative period was uneventful and the patient was discharged on 12th post operative day. Histopathology confirmed the diagnosis of hydatid disease. The patient was followed up for two years without any further development of hydatosis in any organ.Faridpur Med. Coll. J. Jan 2020;15(1): 46-49